A Multicentre Analysis Of Employment Post-Spinal Cord Injury In Malaysia - Chai, Chau Chung; Julia, Patrick Engkasan; Chan, Soo Chin; Nazirah, Hasnan (Wolters Kluwer Health, 2023)
OBJECTIVES: Employment outcome post-spinal cord injury (SCI) varies internationally due to different socioeconomic backgrounds. However, most previous studies were done in developed countries, with limited studies from developing countries like Malaysia. This research aims to study the employment rate, positive determinants of employment, and reasons for unemployment post-SCI in Malaysia.